Pengaruh Promosi Penjualan Terhadap Minat Beli Konsumen Di Burger Bunderan Ciceri, Kota Serang - Qonitah Malina Amalia; Abdul Malik; Endang Dwi Amperawati (Amal Insani Foundation, 2023)
This study aims to examine how much sales promotion influences consumer buying interest at a restaurant that sells burgers in the city of Serang. This food was chosen because the tendency of people to buy this burger is substantial. Moreover, there is a word-of-mouth promotion in it so that the purchasing power of consumers is also influential. To determine the level of influence, a measurement scale is needed. The research methods used included descriptive research design, the Slovin formula for sampling, and data analysis by simple regression analysis method and product moment correlation formulation. Based on data analysis, it is known that sales promotion is stated on a scale of importance, namely at a perfect level. And in the calculation of SPSS software version 16.0, the value of the closeness between sales promotion and purchase intention (variable X to variable Y) shows the medium category. With a weight of R = 0.529. And the two variables' partial KD or Determinant Coefficient is 7.8%, while other factors influence the remaining 92.2192% or 92.22%. So the effect of sales promotion on consumer buying interest at Burger Bunderan Ciceri, Serang City, is very significant.